Diretrizes de gestão para obras habitacionais de interesse social - Pereira, Eliane Alves (2008)
In recent decades, the participation of the Brazilian Government regarding low-income housing projects has suffered changes, following further participation of the private sector by developing products. This fact is leading to a crescent complexity mostly in terms of managing this type of complex, due to the necessity of cost and term reduction to attend most the demands and the necessity to increase the quality and durability of those complexes. Is estimated that the Brazilian housing projects decrease is about 7,9 millions of housing. Moreover, there are and increase of the technologies innovations as well clients crescent requirement for quality. The present study shows the result of a certain case studied, of which the purpose was to diagnose the management problems of the lowincome housing projects construction controlled by private companies, that normally have their own system of management implanted, not forgetting the problems related to application of the plans of quality of works in construction and inspection of this type of complex which is the most important point. The method used is characterized by explorative and qualitative research. The result was presented as to propose Directions of Management for Low-Income Housing Projects. It is expected with this study to contribute for developing an adequate management system for the low-income housing projects complexes which can help the private companies to reduce costs, the waste of materials and reworks, besides improving the quality and productivity of this type of complex and mostly the quality of the housing.